What Resilience Is Not: Uses and Abuses - Magali Reghezza-Zitt; Samuel Rufat; Géraldine Djament-Tran; Antoine Le Blanc; Serge Lhomme (Cybergeo, 2012)
A fashionable concept, resilience is now a must in both academic research and management. However, its polysemy nourishes many debates on its uses, heuristics and operational relevance. The purpose of this article is not to bring these debates to a close. Starting from a cross-disciplinary state of the art, we point out the incompatibilities between certain meanings and uses of the term. These inconsistencies raise theoretical issues, leading some researchers to reject the term for that matter, especially those outside the cindynics field. The analysis of the concept also brings out some methodological pitfalls. These are evident when attempting to translate theory into operational terms. Resilience is indeed seen as a promising response to recurrent difficulties in risk management. Nevertheless, it solves them only partially and produces new ones. Lastly, its implementation involves ethical and political risks. The injunction to resilience that seems to prevail internationally is in fact implying a number of moral and ideological assumptions which are not always clearly stated and remain serious issues.